Epstein-Barr Virus Protein Can Upregulate Cyclo-Oxygenase-2 Expression through Association with the Suppressor of Metastasis Nm23-H1 - Kaul, Rajeev (American Society for Microbiology, 2006)
Previous studies have demonstrated the interaction between the Epstein-Barr virus (EBV) nuclear antigen 3C (EBNA3C) and the metastatic suppressor Nm23-H1 both in vitro and in vivo (C. Subramanian, M. A. Cotter II, and E. S. Robertson, Nat. Med. 7:350-355, 2001). EBNA3C can reverse the ability of Nm23-H1 to suppress migration of Burkitt's lymphoma and breast carcinoma cell lines in vitro. EBNA3C contributes to EBV-associated human cancers by regulating transcription of a number of cellular and viral promoters and by targeting and altering the transcription activities of the metastasis suppressor Nm23-H1. Cyclo-oxygenase-2 (COX-2), an inducible enzyme important in inflammation, is overexpressed in a variety of cancers and can influence cell migration. In this report we show that Nm23-H1 and EBNA3C can modulate expression of COX-2 in the context of EBV infection and transformation. The levels of COX-2 were consistently higher in EBV-positive cells than in EBV-negative cells. Additionally, we show that Nm23-H1 can upregulate the COX-2 promoter element in luciferase reporter assays, whereas EBNA3C alone did not affect the level of response but clearly contributed to an additive increase when coexpressed with Nm23-H1. The downstream effect of COX-2 expression was also evaluated and showed that prostaglandin E(2) levels increased with Nm23-H1 and that there was some level of cooperativity in the presence of EBNA3C. The majority of this response was mediated through the cyclic AMP response element and NF-κB sites. These studies suggest a potential role for COX-2 in EBV-associated human cancers.